The Influence of Occupational Factors to Carpal Tunnel Syndrome on Administrative Workers in A Transportation Manufacturing Company - Farizi Rachman; Am Maisarah Disrinama; Alifia Rojana (Athena: Journal of Social, Culture and Society, 2024)
CTS is arranged in outer muscle problems. This infection is brought about by pressure of the middle nerve at the wrist. Occupational factors are work- related risk factors, such as working quickly, repetitive movements, work stress, work that uses a lot of wrists and vibrations. The motivation behind this study is to decide the impact of word related elements to CTS frequency on regulatory specialists. This study uses cross sectional design with 35 respondents as sample. To determine hand posture was carried out by observation and interpretation with RULA, measurement of repetitive motion use a stopwatch, and work stress use Stress Diagnosis Survey. Utilize the Phalen's Test and the Boston Carpal Tunnel Questionnaire to determine the incidence of CTS. The aftereffect of prescreening on managerial specialists uncovered that 40% laborers are positive for CTS. While the analysis uses binary logistic regression to determine the influence of occupational factors to CTS incident. Variables that influence CTS are repetitive motion of using mouse (p=0.005), repetitive motion of typing (p=0.027), and work stress (p=0.027). Therefore, it is necessary to give recommendations based on related variables (repetitive motion and work stress) in order to minimize the occurrence of CTS.